(untitled) (Fiep Bulletin - online, 2011)
The first objective of this study was to determine the effect of a training program consisting of endurance strength combined with the workload light aerobic exercise training on anthropometric variables such as weight, BMI, waist circumference (WC), fat mass (mGras), Muscle ( MMagra). A second objective was to measure cardiovascular variables such as systolic blood pressure (SBP), diastolic (DBP), resting heart rate (FCR) and six-minute test (T6Min) and, finally, the third objective was to measure variables such as hematological glucose fasting total cholesterol (ColTotal), LDL (ColLDL), HDL (ColHDL) and triglycerides. Study subjects were a group of 28 women with chronic non-communicable assigned to an experimental group (n = 14) and a control group (n = 14). The results showed that the variables that were changed greater significance with the implementation of the training program were weight (p> 0.05), waist circumference (p> 0.05) and total cholesterol (p> 0.05 ) ColLDL (p> 0.05) ColHDL (Sig bilateral = 0.02, P> 0.05) and triglycerides (p> 0.05). Of the most important may be mentioned that the implementation of a training program that includes the ability of resistance exercises performed with an overhead light does not produce muscle hypertrophy and the work in the career of aerobic level of low to moderate intensity can result in beneficial effects on lipid profile.